2021
DOI: 10.3390/healthcare10010061
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Methyl Donors of the Methionine Cycle in Gastrointestinal Infection and Inflammation

Abstract: Vitamin deficiency is well known to contribute to disease development in both humans and other animals. Nonetheless, truly understanding the role of vitamins in human biology requires more than identifying their deficiencies. Discerning the mechanisms by which vitamins participate in health is necessary to assess risk factors, diagnostics, and treatment options for deficiency in a clinical setting. For researchers, the absence of a vitamin may be used as a tool to understand the importance of the metabolic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 163 publications
0
6
0
Order By: Relevance
“…The degradation product of trimethylamine that is exclusively produced by gut microbial metabolism. 39 S-Adenosyl-methionine (SAM) 53 A methylation cycle metabolite and methyl donor, 40 SAM-enzymes are key in bacterial host colonization. 41 Hydroxyphenyl pyruvic acid 53 A gut microbial degradation product of the aromatic amino acid tyrosine.…”
Section: Effect Modification By Race Gender and Agementioning
confidence: 99%
“…The degradation product of trimethylamine that is exclusively produced by gut microbial metabolism. 39 S-Adenosyl-methionine (SAM) 53 A methylation cycle metabolite and methyl donor, 40 SAM-enzymes are key in bacterial host colonization. 41 Hydroxyphenyl pyruvic acid 53 A gut microbial degradation product of the aromatic amino acid tyrosine.…”
Section: Effect Modification By Race Gender and Agementioning
confidence: 99%
“…DNA methyltransferases (DNMTs) transfer the methyl group to cytosine and convert SAM to S-adenosyl homocysteine (SAH) which is further degraded to homocysteine (HCY) by SAH hydrolase ( 16 ). During these processes, vitamin B6 serves as a co-factor ( 17 ). It’s reported that excessive methionine and vitamin B6 intake induces hyper-methylation ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…During these processes, vitamin B6 serves as a co-factor (17). It's reported that excessive methionine and vitamin B6 intake induces hypermethylation (18).…”
Section: Melatonin May Play a Key Role In The Genomic Hyper-methylati...mentioning
confidence: 99%
“…Methionine produces strong antioxidative metabolites such as glutathione, cysteine and sulphate through the trans-sulphuration pathway. Previous studies have demonstrated the ameliorative effect of methyl and S-adenosylmethionine produced by the methionine cycle on systemic inflammation and liver damage [ 41 ]. The methionine cycle is widely active in Saccharomyces cerevisiae [ 42 ].…”
Section: Discussionmentioning
confidence: 99%